The Legitimacy of Peace Operations in Volatile Environments: Between State-Centred and People-Centred Standards - Gelot, Ludwig (Journal of Regional Security, 2018)
Peace operations are increasingly multi-dimensional and are affecting ever more as- pects of life at the grassroots level. While this evolution is necessary, it has created a tension in the field of legitimacy. Indeed, how can the United Nations possibly legitimise its actions in a domain traditionally subject to domestic laws and norms? International and domestic standards of legitimacy are clashing but neither of them is fully adapted to the particular case of peace op- erations. This article outlines a third approach to legitimacy centred on the UN Charter which incorporates the views of the entire legitimacy constituency of peace operations deployed in volatile environments.